Malocclusion impacts the quality of life of Peruvian school children. A cross-sectional study. - Luz Mamani; Sively Mercado; Jorge Mercado; Katty Ríos (Universidad de Concepción., 2017)
Objective: To assess the impact of malocclusion considering the orthodontic treatment need (IOTN) on the oral health related quality of life evaluated with the Child Perceptions Questionnaire in students aged 11 to 14 years (CPQ 11-14 ) of the Peruvian public schools in the city of Juliaca. Materials and methods: A cross-sectional study was performed. The sample included 354 students. The data were obtained from the tool of self-perception using the aesthetic component (AC) and the oral health component (DHC) from the IOTN, and the CPQ 11-14. For the data analysis the Kruskal Wallis test was used (p<0.05). Results: The value of the impact on the quality of life was higher in the dimension moderate treatment need with 56.08; followed by need for treatment with 55.56 (p<0.001). Conclusion: Malocclusion affects the quality of life of students aged 11 to 14 years in Peruvian public schools of the city of Juliaca.